Diversity and Prevalence of Trematode Infections in Freshwater Gastropods of the Gharb Region, Morocco (2012-2013) - Barkia, Hicham; Barkia, Abdelaziz; Yacoubi, Rajae; Guamri, Youssef EL; Madhi, Youssef El; Belghyti, Driss (Contemporary Research and Perspectives in Biological Science Vol. 6, 2024)
The majority of studies on trematode infections in snails in Morocco have focused on those of medical and veterinary importance, while little information on other trematode species is available in existing literature. Several studies indicate that global climate change may alter the distribution and prevalence of medical and veterinary significance trematodes, potentially even increasing their occurrence in certain regions. In the summer of 2012 and the spring of 2013, a snail survey aimed at determining relationships between the distribution of molluscan fauna, various environmental factors and trematode infection was carried out in the Gharb area, Morocco. The molluscan fauna consisted of eleven species belonging to 6 families, (including 9 gastropods and 2 bivalves). Cercariae belonging to five families were collected. Only Melanopsis praemorsa, Lymnaea peregra and Lymnaea truncatula issued the cercariae. No case of mixed-species infections was found. The present study, the first of its kind in the Gharb region, paved the way for other studies to learn information about the distribution and ecology of freshwater molluscs in the region. This study will serve to stimulate further work on patent and pre-patent infections of snail hosts; larval behaviour and morphology, geographical distribution of trematodes; infections in human beings, livestock and wildlife; and clinical manifestations of trematode infection in the Gharb area.